Consórcios de alface crespa e pepino em função da População do pepinoe época de cultivo - Rezende, Bráulio Luciano Alves; Filho, Arthur Bernardes Cecílio [UNESP]; De Queirós Pôr, Diego Resende; Barros Jr., Aurélio Paes; Da Silva, Gilson Silverio [UNESP]; Barbosa, José Carlos [UNESP]; Feltrim, Anderson Luis [UNESP] (My University, 2010)
With the aim of evaluating the yields of cucumber and lettuce for two cucumber population densities, intercropped with lettuce under protected environment, and for two growing seasons, one from August to November 2005 and the other from February to May 2006, four experiments were conducted at UNESP, Jaboticabal, SP, Brazil. The experimental design in each case was of randomized complete blocks with the treatments arranged in 2.4+1 factorial scheme and with four replications, where the first factor was given by two cropping systems (intercropping and individual crop), the second one for four transplanting dates for lettuce in relation to cucumber (0, 10, 20 and 30 days), and an additional treatment of the sole cucumber crop. Total yield, commercial and misshapen cucumber fruits were not affected by the presence of lettuce. The growing season influenced the commercial yield of cucumber, which is greater from February to May. The yield of lettuce was affected by the date of transplantation (establishment of the intercropping), with further reduction as the transplantation of lettuce was delayed in relation to that of cucumber. Lettuce grown in intercropping with cucumber in the second growing season did not have commercial quality, due to the deep shade provided by the cucumber.
Intercropping of curly lettuce and cucumber as a function of the cucumber population and growing season